135 Identification of patients with advanced liver disease nearing the end of life within a secondary care hepatology specialist service. (14th March 2023) - Jordan, Roberta; Millson, Charles; Orange, Dawn; Gott, Naomi; Sartain, Kathryn; Sainty, Martin; Daniel, Sunitha
Abstract : Introduction: Non-malignant liver disease is the 3rd most common cause of death in working-age adults. Those affected spend significant durations in hospital in the last year of life, focusing on disease modification with little regard to symptom management and quality of life. We aimed to estimate the mortality rate for patients with cirrhosis within a secondary care hepatology specialist service. We also quantified the number of inpatients meeting the criteria of screening tools designed to identify patients with liver disease nearing the end of life. Methods: We used locally collected routine data to estimate the mortality rate for patients known to the hepatology service with cirrhosis. We used the Supportive and Palliative Care Indicators Tool (SPICT) and Bristol Screening Tool (BST) criteria to identify inpatients with liver disease who may be nearing the end of life, analysing patient records prospectively for three days over a three-week period (4–18/8/22) on one 25-bed hepatology/gastroenterology ward. Results: Using the 586 patients known to have cirrhosis on the local database (1/9/22) as a denominator, we estimated a mortality rate of 10% in 2021, 7% in 2020 and 8% in 2019. From our inpatient analysis, we identified 37 patients with liver disease, 25 after removing duplicates (patients admitted ≥1 day). Of these 25, 9 met SPICT, 5 met BST and 5 met both criteria. Conclusions: We have identified a significant mortality rate of up to 10% of patients with cirrhosis being managed by a secondary care hepatology service. Of those admitted with liver disease, potentially one-third are nearing the end of life. This emphasises the importance of considering a parallel planning approach with disease modification alongside palliative and end of life care. Locally, we are developing an advanced liver disease multidisciplinary team who will use SPICT to better identify patients and facilitate this approach.